2018
DOI: 10.3390/ijerph16010048
|View full text |Cite
|
Sign up to set email alerts
|

Eudaimonic Well-Being and Coping with Stress in University Students: The Mediating/Moderating Role of Self-Efficacy

Abstract: The importance of personal psychological resources in preventing academic stress has enjoyed little attention to date, despite the high rates of stress that exist among university students. This article analyzes the effect of eudaimonic well-being on the use of adaptive strategies for coping with academic stress. Moreover, it analyzes the role of self-efficacy as a mediator and moderator of this relationship. In the mediation model, gender is included as a co-variable; in the moderation model, gender is includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 71 publications
(89 reference statements)
1
54
0
2
Order By: Relevance
“…Coping strategies are a psychological construction referring to knowledge, skills and strategic behaviors that people use to manage emotions occurring within a situation of stress (Fimian et al, 1989;Chartier et al, 2011;Freire et al, 2018); for this reason, they are considered meta-emotional skills (de la Fuente et al, 2017a). Multiple models have been proposed for categorizing these skills, beginning with the initial model proposed by Lazarus andFolkman (1984/1986) and Lazarus (1999).…”
Section: Coping Strategies As a Variable Of The Teaching And Learningmentioning
confidence: 99%
“…Coping strategies are a psychological construction referring to knowledge, skills and strategic behaviors that people use to manage emotions occurring within a situation of stress (Fimian et al, 1989;Chartier et al, 2011;Freire et al, 2018); for this reason, they are considered meta-emotional skills (de la Fuente et al, 2017a). Multiple models have been proposed for categorizing these skills, beginning with the initial model proposed by Lazarus andFolkman (1984/1986) and Lazarus (1999).…”
Section: Coping Strategies As a Variable Of The Teaching And Learningmentioning
confidence: 99%
“…Prior research on motivational-affective factors in university learning has also stressed the importance of particular aspects of how university students cope with stress: religious coping (Francis et al, 2018); the role of health habits as a coping strategy [43]; coping in relationship to well-being [44][45][46]. Also, have analyzed the predictive role of achievement emotions in coping strategies and in motivational states of engagement-burnout [47].…”
Section: Coping Strategies As a Meta-emotional Variable Of The Learnimentioning
confidence: 99%
“…On the other hand, interventions focused on modifying emotional regulation strategies could be designed to address aspects like activation or attention, or offer specific training to enhance performance. Such interventions could have an individual, group or online format, the latter showing demonstrated effectiveness in recent years [46,74].…”
Section: Implications and Applicabilitymentioning
confidence: 99%
“…Braaten et al [17] point out, while hedonic well-being is also important for students' cognitive-affective balance during university years, it is eudemonic goals that can have long-lasting effects on the overall satisfaction with life. In an empirical study, Freire et al [18] found that eudemonic values alongside with self-efficacy are instrumental to deal with stress during university life. In Delle Fave et al's [19] research, along with Norway and Croatia, Hungarian respondents placed the biggest emphasis on the Health domain.…”
Section: Literature Reviewmentioning
confidence: 99%